Optimized negative thermal expansion induced by gradual intermetallic charge transfer in Bi1−xSbxNiO3. (10th May 2018) - Nishikubo, Takumi; Sakai, Yuki; Oka, Kengo; Mizumaki, Masaichiro; Watanuki, Tetsu; Machida, Akihiko; Maejima, Naoyuki; Ueda, Shigenori; Mizokawa, Takashi; Azuma, Masaki
Abstract: Negative thermal expansion (NTE) induced by intermetallic charge transfer between Bi 5+ and Ni 2+ was observed in Bi1− x Sb x NiO3 ( x = 0.05 and 0.10). Bi 3+ and Bi 5+ had a long-range ordering in the low-temperature phase of Bi0.95 Sb0.05 NiO3 while the ordering was short-range in Bi0.9 Sb0.1 NiO3 . The latter compound exhibited a continuous NTE with a linear coefficient of thermal expansion (CTE) of αL = −106 ppm K −1 without temperature hysteresis in a wide temperature range of 200–320 K.